Effect of Glycosaminoglycans on Thrombin- and Atroxin-Induced Fibrin Assembly and Structure - Carr, Marcus E, Jr.; Powers, Patrick L (Thrombosis and Haemostasis, 1989)
This study was performed to quantitate the impact of several glycosaminoglycans (GAG) on fibrin assembly and structure. Gel formation was monitored as the increase in optical density at 633 nm subsequent to thrombin (2 NIH u/ml) or atroxin (0.10 mg/ml) addition to solutions of buffered fibrinogen (1 mg/ml) or plasma. Gel absorbance was measured as a function of wavelength (400 to 800 nm) and gel fiber diameter and mass/length ratio (μ) were calculated. Chondroitin sulfate A (CSA)shortened the lag phase, enhanced the maximal rate of turbidity increase, and increased the final gel turbidity of fibrin gels formed by thrombin or atroxin. CSA (16 mg/ml) increased fiber μ from 1.3 to 3.1 × 1013 dalton/cm and fiber radius from 6.0 to 8.6 × 10-6 cm in thrombin-induced gels. μ increased from 0.7 to 2.7 × 1013 dalton/cm and fiber radius from 4 to 7.8 × 10-6 cm for atroxin-induced gels. Above 16 mg/ml, CSA caused fibrinogen precipitation in purified solutions but not in plasma. CSA inhibited thrombin-induced plasma clotting of plasma but effects in atroxin-mediated plasma gels paralleled those seen in purified solutions. Chondroitin sulfate B (CSB)-induced changes in fibrin were similar but slightly less dramatic than those seen with CSA. μ increased from 0.9 to 2.0 × 1013 dalton/cm for thrombin-induced fibrin gels and from 0.8 to 2.3 × 1013 dalton/cm for atroxininduced gels. Low molecular weight heparin (Mr = 5100) slowed fibrin assembly and reduced fiber size by 50% in thrombininduced gels. Changes in μ of atroxin-induced gels were much less pronounced (<20%). This study documents pronounced GAGinduced changes in fibrin structure which vary with GAG species and may mediate significant physiologic functions.
Keywords: Chondroitin sulfate A; Chondroitin sulfate B; Heparin